Performance Analysis of Hybrid Spectrum Sharing in Cognitive Radio Based Wireless Regional Area Network - Afzal, H.; Mufti, M. R.; Ahmed, K. T.; Ajmal, S.; Yousaf, M. (The Nucleus, 2020)
Cognitive radio (CR) network is the footstep and essential need of the new wireless emerging technologies like the Wireless Sensor Network (WSN), Internet of Things (IoT), Bluetooth, and Vehicular Ad Hoc Network (VANET). Due to tremendous progress in the number of wireless devices and their traffic, large scale usage of these technologies may soon cause a shortage of spectrum as all these technologies use unlicensed bands. So, CR is a vital choice for their survival. In this paper, we address the Quality of Service (QoS) parameters related to spectrum sharing among multiple Customer Premises Equipments (CPEs) in the context of CR based Wireless Regional Area Network (WRAN) using trunking theory. For this purpose, an analytical framework is developed to obtain QoS parameters such as traffic intensity, the total number of users in the network, and time to associate with the base station (BS). For a progressive environment, particularly the increase in the population of WRAN, we also analyzed channel access time and received signal strength (RSS) for CPEs. Two types of centralized trunked CR systems: 1) queued and 2) non-queued systems are investigated and this model can be helpful for the BS in scheduling the required number of channels depending upon Grade of Service (GoS) and the total number of users. The numerical results validate our model.